Simplify the following:
k - 2 (k - (2 - k)) - 2
-(2 - k) = k - 2:
k - 2 (k + k - 2) - 2
Grouping like terms, k + k - 2 = (k + k) - 2:
k - 2 ((k + k) - 2) - 2
k + k = 2 k:
k - 2 (2 k - 2) - 2
-2 (2 k - 2) = 4 - 4 k:
k + 4 - 4 k - 2
Grouping like terms, k - 4 k - 2 + 4 = (4 - 2) + (k - 4 k):
(4 - 2) + (k - 4 k)
k - 4 k = -3 k:
-3 k + (4 - 2)
4 - 2 = 2:
Answer: 2 - 3 k
Click on the picture! This is the explanation in accident I deleted it hope it helps!
Answer:
Step-by-step explanation:
4/6=2/3
2/3=2/3
scale factor=2/3
A=3
b=-6
c=1
x=(-b±<span>√(b^2-4ac))/2a
x=(6</span>±√(36-12))/(6)
x=(6±√(24))/(6)
x=(6±2√(6))/(6)
x=(3±√(6))/(3)
x≈1.82
x≈<span>.184</span>
Step-by-step explanation:
the temperature fell 24°F in 7 hours.
so, when it had -2°F at 7pm, it had 24° more 7 hours before that.
that is 22°F at 12pm (noon).